Atividade enzimática de solo e sua relação com sistemas de plantas de cobertura em período outonal - Gerlach, Luís Felipe Rossetto (2022)
The wheat crop is of great importance for the agricultural sustainability of southern Brazil, and the search for increases in its productivity comes into the agenda with new studies. The use of cover crop systems becomes a very efficient alternative in improving soil quality in order to increase the productive potential of the successor crops. Bioindicators have shown a good relationship with soil quality, with enzymatic activity being one of the main bioindicators used due to its high sensitivity in response to different management systems. Thus, this work aimed to evaluate different systems of cover crops in autumn, and their relationship with enzymatic activity of arylsulfatase and beta-glucosidase and with wheat productivity in the north of the state of Rio Grande do Sul. The study was conducted in the agricultural year of 2021 in a Red Latosol, in an irrigated area of the company Sementes Aurora de Cruz Alta, 35 different systems of cover plants were implanted, being 18 single systems and 17 intercropped. Georeferenced soil samples from 0 to 0.15 m were collected to evaluate the enzymatic activity of arylsulfatase and beta-glucosidase, with 3 replications per cropping system, totaling 105 sampling points, being in wet and dry season (May and December 2021, respectively), where the enzymatic activity of arylsulfatase and beta-glucosidase, wheat yield and OM and S contents in the soil were evaluated. Data from the May collection were submitted to descriptive statistical analysis, multivariate analysis of clustering by dendrograms for single plant systems and for intercropped plant systems and t-test analysis for independent samples between the means of each group. In addition, enzymatic activity data from both collections were subjected to descriptive analysis, geostatistics and Spearman correlation. In chapter one it was observed that the enzymatic activities for the two sampling periods showed variability. Only significant correlations were observed between the different enzymes within the same sampling period, and in the wet season the enzymes had a correlation of 0.902 and in the dry season of 0.745. In chapter two, short-term effects on enzymatic activity and wheat productivity can be seen, regardless of the management system. Observing different results in plants of the same botanical family. With this, it is clear that the biological attributes have great vertical and temporal variability in agricultural areas, where enzymatic activities present high correlation when sampled at the same time. The arylsulfatase and beta-glucosidase activities were influenced by the cover crops systems, showing no influence of soil S and MO contents. Enzyme activity shows great variability, being mainly dependent on management and season. Therefore, in the short term, cover crops affect enzymatic activity and tend to affect wheat productivity.